Harmony in the Family: Indicators of Marriage Success in Cultural and Religious Foundations in Bangladesh - M Mahmudulhassan; Muhammad Abuzar (Demak Universal Journal of Islam and Sharia, 2024)
This study aims to investigate the concept of harmony in the family in the context of Islamic culture and religion in Bangladesh. The research methods used include surveys, interviews, and document analysis to understand the formulas and indicators of marriage success within the foundation of Islamic culture and religion. The results showed that family harmony in Bangladesh is strongly influenced by religious values and strong cultural traditions. The formula for successful marriage includes good communication, mutual understanding, fidelity, and active involvement in family activities. Success indicators include happiness and peace in the marriage relationship, as well as harmony in daily interactions between married couples and other family members. Thus, the study provides valuable insights into how Islamic culture and religion shape the concept of harmony in families in Bangladesh.